2002
DOI: 10.5194/npg-9-367-2002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical wind wave model with a dynamic boundary layer

Abstract: Abstract.A modern version of a numerical wind wave model of the fourth generation is constructed for a case of deep water. The following specific terms of the model source function are used: (a) a new analytic parameterization of the nonlinear evolution term proposed recently in Zakharov and Pushkarev (1999); (b) a traditional input term added by the routine for an atmospheric boundary layer fitting to a wind wave state according to Makin and Kudryavtsev (1999); (c) a dissipative term of the second power in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In ( 5), c ph (ω) is the phase velocity as function of frequency, taken at the peak frequency of wind-wave spectrum, ω p ; and W 10 is the wind speed at the standard horizon, z=10 m. Herewith, in Wu (1975) it was clearly shown that the drift velocity, U d , decreases with the wave-fetch increasing, what is in a good agreement with the known variability of the friction velocity (see survey of data in (Polnikov et al, 2003) and detailed parametrization in (Polnikov , 2013)).…”
Section: A Formulas For U Dsupporting
confidence: 76%
See 1 more Smart Citation
“…In ( 5), c ph (ω) is the phase velocity as function of frequency, taken at the peak frequency of wind-wave spectrum, ω p ; and W 10 is the wind speed at the standard horizon, z=10 m. Herewith, in Wu (1975) it was clearly shown that the drift velocity, U d , decreases with the wave-fetch increasing, what is in a good agreement with the known variability of the friction velocity (see survey of data in (Polnikov et al, 2003) and detailed parametrization in (Polnikov , 2013)).…”
Section: A Formulas For U Dsupporting
confidence: 76%
“…It can be assumed that all the dependences of drift velocity on the wave state are "hidden" in the direct proportionality between U d and friction velocity *a u , whilst the latter, as is well known, depends explicitly on the above-mentioned wave parameters: H, ε and A (see references in Polnikov et al (2003), Polnikov (2013)). However, the absence of direct empirical dependences of U d on wave parameters, in our opinion, requires its justification basing on specialized experiments for their determination.…”
Section: A Formulas For U Dmentioning
confidence: 99%
“…By modifying the wind wave model -WAM, a series of numerical experiments [5,37] are carried out for verification of a proposed source function. Verification is done on the basis of comparison of the results of wave simulation for a given wind field with the buoy observation data obtained in three oceanic regions (Barents Sea, eastern and western parts of North Atlantic Ocean).…”
Section: Improved Third Generation Modelsmentioning
confidence: 99%
“…as proposed by Jenkins and Phillips [2001] on dimensional grounds, this formulation for the nonlinear energy transfer term is equivalent to the diffusion approximation of Polnikov [2002] and Polnikov et al [2002]. Equation ( 5) is also valid when surface tension effects are included, in which case it can be written as…”
Section: Source Functionmentioning
confidence: 99%
“…Jenkins and Phillips [2001] showed that a nonlinear source term of the form conserves energy, action, and momentum for any function ψ ( k ) that goes to zero rapidly enough as k → 0 and k → ∞. Using the gravity wave dispersion relation and defining as proposed by Jenkins and Phillips [2001] on dimensional grounds, this formulation for the nonlinear energy transfer term is equivalent to the diffusion approximation of Polnikov [2002] and Polnikov et al [2002]. is also valid when surface tension effects are included, in which case it can be written as where τ is the ratio of the surface tension to the density of water.…”
Section: Source Functionmentioning
confidence: 99%